2020
DOI: 10.1038/s42004-020-0284-3
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of siderite to goethite by humic acid in the natural environment

Abstract: Humic acid (HA) is particularly important in iron-bearing mineral transformations and erosion at the water-mineral boundary zone of the Earth. In this study, three stages of the possible pathway by which HA causes mineral transformation from siderite to goethite are identified. Firstly, a Fe(II)-HA complex is formed by chelation, which accelerates the dissolution and oxidation of Fe(II) from the surface of siderite. As the Fe(II)-HA complex retains Fe atoms in close proximity of each other, ferrihydrite is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 57 publications
(85 reference statements)
0
21
0
Order By: Relevance
“…The binding energy peaks located at 710.6 and 724.4 eV are attributed to the formation of surface Fe 2+ species. 31 The weaker peaks at 712.7 and 726.8 eV correspond to the surface Fe 3+ species, which is also verified by the occurrence of the satellite peak at 717.2 eV. 32 The curve fittings of the XPS spectrum showed that both Fe 2+ and Fe 3+ species were generated on the surface of lf-Fe/PI HNs with the atomic ratio of Fe 2+ /Fe 3+ of 1.5 : 1.…”
Section: Resultsmentioning
confidence: 77%
“…The binding energy peaks located at 710.6 and 724.4 eV are attributed to the formation of surface Fe 2+ species. 31 The weaker peaks at 712.7 and 726.8 eV correspond to the surface Fe 3+ species, which is also verified by the occurrence of the satellite peak at 717.2 eV. 32 The curve fittings of the XPS spectrum showed that both Fe 2+ and Fe 3+ species were generated on the surface of lf-Fe/PI HNs with the atomic ratio of Fe 2+ /Fe 3+ of 1.5 : 1.…”
Section: Resultsmentioning
confidence: 77%
“…These studies have indicated that the majority of fresh flocs formed by coagulation are composed of thousands of primary spherical nanoparticles (Su et al, 2017;Wu et al, 2019), and that with aging some crystallization of nanoparticles occurs and changes in their structures occur (Yu et al, 61 2016a;Yu et al, 2018). In addition, it was found that organic matter, such as humic-like substances which exist ubiquitously in surface water, can affect the aggregation between nanoparticles (Bian et al, 2011;Jarvis et al, 2005), and the 64 crystallization and transformation of Fe (hydr)oxides (Xing et al, 2020). 65…”
Section: Introductionmentioning
confidence: 99%
“…Figure f shows that 10 mg·L –1 HA promoted the release of BPS from all MPs compared to that in DI water. The ·OH generation concentration in the suspension of MPs was increased after addition of 10 mg·L –1 HA (Figure S5), because the chromophores in HA, such as aromatic rings, hydroxyl groups, and carboxyl groups, could absorb light energy and promote ·OH generation reactions. The generated radicals thus enhanced the released concentrations of BPS. Higher concentrations (20 and 50 mg·L –1 ) of HA were found to inhibit the release of BPS (Figure S6).…”
Section: Resultsmentioning
confidence: 99%